Social Determinants of Health - Balogh, Pamela (My University, 2021)
The Social Determinants of Health (SDOH) are non-medical factors that impact our health outcomes and play a significant role in a person's ability to get and stay healthy. Standardizing the screening for SDOH can help understand how SDOH affects a patient's health, population, and community. A quality improvement project was designed to standardize a screening process for four primary SDOH domains: food security, housing, transportation, and interpersonal safety. Furthermore, determine a need followed by appropriate referrals to community resources within a local health department. The project included a staff education session, distribution of SDOH screening tools within various languages, and a handout of local resources and services. Process measures and outcomes guided the project implementation. Three clinics performing SDOH screenings were tracked over 12 weeks. Out of 965 eligible patients seen in the three clinics, 310 were screened (32%), and 142 referrals (46%) were made to assist patients with one or more SDOH. The benefits provided care of the whole person and recognition for optimal health outcomes—furthermore using a wealth of screening, referrals, and outcomes to identify interventions aligned with the triple aim. It improves patients' health and identification and may benefit from more support, particularly those underserved, reducing costs in patient care with reduced admissions, readmissions, and emergency room utilization while improving their experience and healthcare connections through the local health department.
Keywords: social determinants of health, food security, housing, transportation, interpersonal safety